Stimbut: Initiation of a Sustainable Business Strategy Model in Improving MSME Capability to Meet Consumer Expectations - Wibowo, Frendy; Putra, Febrianur Ibnu Fitroh Sukono; Izzudien, Muhammad; Sulastri, Sulastri (Universitas Dian Nuswantoro Semarang, 2023)
A sustainable business strategy is inevitable for 21st-century businesses. Consumers expect MSMEs to adopt sustainable strategies but realizing one's needs is the only impetus for any consumer. Thus, there is a gap between business sustainability practices and consumer expectations. This research identifies strategic sustainable business strategies to be integrated into business practices. This type of research uses exploratory qualitative methods. The type of data is primary data which is a direct answer from the informant. The data collection technique uses an interview method. The sampling design used non-probability sampling (snowball). The analysis technique is through data collection, data reduction, data presentation, and concluding because it can explain, assess, and visualize superior MSME empowerment modeling. The results of this study indicate that four strategies can be applied by MSMEs, including New vs. returning visitors, Bounce rate, Abandonment rate, and cost per conversion. The results of this study can contribute to the development of a technology-based sustainable business strategy which is expected to become the primary role model in increasing the competitiveness of MSMEs. Keywords:business strategy, competitiveness, capability, digital, sustainability